2021
DOI: 10.17066/tpdrd.1050742
|View full text |Cite
|
Sign up to set email alerts
|

Development of Online Trolling Scale: Validity and Reliability Study

Abstract: This study aims to develop a valid and reliable measurement tool to determine trolling in online environments. Two different study groups were used in the study. The study group for the exploratory factor analysis consisted of 493 university students (72.2% female; 27.8% male). The study group for confirmatory factor analysis consisted of 690 university students (71.7% female; 28.3% male). As a result of the exploratory factor analysis, it was seen that it consisted of 16 items and 3 sub-dimensions that explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…However, additional research is needed to replicate these results. Moreover, as past research showed (Hamarta et al, 2021; Sanfilippo et al, 2018), trolling is a multidimensional construct, and the present research demonstrated that sarcastic trolling is one dimension of trolling. Finally, a social desirability scale was used to see whether individuals performing trolling were concerned with obtaining social approval and there was a negative association between trolling measures and social desirability in this study.…”
Section: Discussionsupporting
confidence: 72%
“…However, additional research is needed to replicate these results. Moreover, as past research showed (Hamarta et al, 2021; Sanfilippo et al, 2018), trolling is a multidimensional construct, and the present research demonstrated that sarcastic trolling is one dimension of trolling. Finally, a social desirability scale was used to see whether individuals performing trolling were concerned with obtaining social approval and there was a negative association between trolling measures and social desirability in this study.…”
Section: Discussionsupporting
confidence: 72%
“…This proactive–reactive distinction of trolling indicates that the same trolling behavior can be performed in either a proactive or reactive manner. For example, this two-dimensional framework could potentially be applied to explore other proactive vs. reactive types of deceptive or sarcastic trolling (Demsar et al, 2021; Hamarta et al, 2021; Manuoğlu & Öner-Özkan, 2022), thereby opening avenues for further research. Furthermore, our findings demonstrate that the concept of offline proactive and reactive aggression can be extended to the study of online hostility (Dodge et al, 1997; Raine et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Demsar et al (2021) categorized online trolling into three types: antagonism (inciting hatred), deception (purposefully deceiving others), and vigilantism (seeking revenge). Similarly, Hamarta et al (2021) developed a trolling scale with three subtypes: harm-, provocation-, and fraudulence-based.…”
Section: Online Trolling: a New Typologymentioning
confidence: 99%
See 2 more Smart Citations